Innovation practices in a non-profit portuguese organization - Barbosa, Fernando de Oliveira (2014)
This article is a case study of a Social Economic Organization, where we will examine, in the light of the literature on strategic management, and innovation, its organizational change, which was critical to ensure its survival. Through this case study we intend to increase the understanding and the knowledge on the main motivations, barriers and facilitating factors leading to the improvement of the quality of the services, and the efficiency of the management of the Social Economy Organizations, which contribute to its competitiveness and sustainability. The case study highlights a number of best practices in the design of structured innovation processes, which were supported by the Portuguese Program Q3-Qualifying the Third Sector, which may help similar organizations to improve their innovation and organizational processes, which are essential to increase their competitiveness and sustainability.